Mechanism of strain relaxation in BaSi2 epitaxial films on Si(111) substrates during post‐growth annealing and application for film exfoliation. Issue 12 (4th November 2013) - Hara, Kosuke O.; Usami, Noritaka; Nakamura, Kotaro; Takabe, Ryouta; Baba, Masakazu; Toko, Kaoru; Suemasu, Takashi; Maeda, Yoshihito; Suzuki, Motofumi
Abstract Strain accumulation and relaxation in BaSi2 epitaxial films on Si(111) substrates during thermal treatments have been studied. The 2θ –ω X‐ray diffraction analysis shows that the film‐normal lattice parameters (a) in epitaxial films are smaller than that in the bulk, indicating in‐plane tensile stress is accumulated in the asgrown films. Resultant curvature of the substrate has been observed by spatially‐resolved X‐ray rocking curve analysis. This strain is relaxed by post‐growth annealing through cracking. The conditions of cracking are revealed in terms of the film thickness and annealing temperature, from which the mechanism of strain relaxation is discussed. It is found from the tape test that the films with cracks can be exfoliated with an adhesive tape. The free‐standing annealed films are subjected to the microwave‐detected photoconductivity decay measurement, which reveals a long minority‐carrier lifetime of 5 μs. (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)